2008
DOI: 10.1126/science.1158540
|View full text |Cite
|
Sign up to set email alerts
|

Large and Rapid Melt-Induced Velocity Changes in the Ablation Zone of the Greenland Ice Sheet

Abstract: Continuous Global Positioning System observations reveal rapid and large ice velocity fluctuations in the western ablation zone of the Greenland Ice Sheet. Within days, ice velocity reacts to increased meltwater production and increases by a factor of 4. Such a response is much stronger and much faster than previously reported. Over a longer period of 17 years, annual ice velocities have decreased slightly, which suggests that the englacial hydraulic system adjusts constantly to the variable meltwater input, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
300
4
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(327 citation statements)
references
References 13 publications
19
300
4
4
Order By: Relevance
“…The ablation zone is up to 150 km wide in the dry southwest and northeast, and narrower than a single model gridpoint ($11 km) in the wet southeast and extreme northwest. The few available SMB observations from the ablation zone range from À1350 kg m À2 yr À1 on Storstrøm-men in the northeast [Bøggild et al, 1994] to <À3500 kg m À2 yr À1 along the K-transect in the southwest [van de Wal et al, 2005[van de Wal et al, , 2008. These are in good agreement with the map, although the width of the ablation zone in the southwest is overestimated by $20 km and the SMB gradient is underestimated in the lower ablation zone ( Figure S2d).…”
Section: Surface Mass Balancesupporting
confidence: 72%
“…The ablation zone is up to 150 km wide in the dry southwest and northeast, and narrower than a single model gridpoint ($11 km) in the wet southeast and extreme northwest. The few available SMB observations from the ablation zone range from À1350 kg m À2 yr À1 on Storstrøm-men in the northeast [Bøggild et al, 1994] to <À3500 kg m À2 yr À1 along the K-transect in the southwest [van de Wal et al, 2005[van de Wal et al, , 2008. These are in good agreement with the map, although the width of the ablation zone in the southwest is overestimated by $20 km and the SMB gradient is underestimated in the lower ablation zone ( Figure S2d).…”
Section: Surface Mass Balancesupporting
confidence: 72%
“…Numerous studies in Greenland have revealed the intimate link between surface melt and ice dynamics, whereby surface meltwater reaching the bed perturbs water pressure at the ice bed interface and thus causes a change in ice motion [8,45,55,79]; the fundamental link being that an increase in basal water pressure causes an increase in ice bed separation (i.e. a degree of floatation), a reduction in the local ice bed friction and the overlying ice therefore accelerates.…”
Section: The Greenland Ice Sheet's Dynamic Response To Meltwater Inputsmentioning
confidence: 99%
“…Interpretation of field observations is complex, with some studies suggesting that more melt will increase annual flow [12][13][14] while others suggest the opposite [15][16][17][18] . Current theoretical understanding of GrIS basal hydrology calls on the evolution of the subglacial drainage system from low to high hydraulic efficiency, to accommodate for melt supply variability over the ablation season [19][20][21] , although limited direct observations of the basal environment do not fully verify this model [22][23][24] .…”
mentioning
confidence: 99%